PENGEMBANGAN AUDIOBOOK DIGITAL BERBANTUAN PUZZLE FLASHCARD UNTUK MENINGKATKAN PEMAHAMAN IDE POKOK PARAGRAF DI KELAS IV SDN KEBON BARU 07 JAKARTA - Monika, Sindi; Yuli Satriyani, Febrianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to develop an innovative learning medium in the form of a digital audiobook assisted by puzzle flashcards to improve students’ understanding of paragraph main ideas in Indonesian language learning. The research used a Research and Development (R&D) approach with the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation. The ADDIE model was chosen to ensure a systematic and structured development process.The study was conducted in Grade IV of SDN Kebon Baru 07 Jakarta with 27 students. Data were collected through observation, interviews, and documentation. Expert validation results indicated that the media were categorized as very valid. Product trials at both small-scale and large-scale levels, along with student and teacher responses, showed that the media were very effective. The N-gain analysis revealed an average score of 0.65 (65%) in the small-scale trial and 0.68 (68%) in the large-scale trial, indicating that the media were moderately effective.